2019
DOI: 10.7717/peerj.7098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of assisted walking-movement in patients with genetic and acquired neuromuscular disorders with the motorised Innowalk device: an international case study meta-analysis

Abstract: People with physical disabilities (PD) suffer from consequences due to lack of physical activity and consequently, are at increased risk of chronic diseases. We aimed to evaluate the ability of a motorised assistive device for dynamic standing with weight-bearing in addition to standard state-of-the-art therapy to improve clinical outcome in a meta-analysis of available studies. A total of 11 studies were identified from different European countries analysing the effect of the dynamic device Innowalk. Raw data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Of note there were six participants who improved their bilateral knee ranges, and four participants who improved their bilateral ankle ROM with knee flexed by five or more degrees between timepoints 1 and 2. This is in line with another study which demonstrated that regular usage of the IP in a paediatric population, PROM of joints in the lower extremities improves (Schmidt‐Lucke et al, 2019). Bilateral knee ROM was not maintained 3 months post‐intervention, reducing up to seven degrees, suggesting that a 3‐month break from using the IP could be detrimental to knee ROM.…”
Section: Discussionsupporting
confidence: 90%
“…Of note there were six participants who improved their bilateral knee ranges, and four participants who improved their bilateral ankle ROM with knee flexed by five or more degrees between timepoints 1 and 2. This is in line with another study which demonstrated that regular usage of the IP in a paediatric population, PROM of joints in the lower extremities improves (Schmidt‐Lucke et al, 2019). Bilateral knee ROM was not maintained 3 months post‐intervention, reducing up to seven degrees, suggesting that a 3‐month break from using the IP could be detrimental to knee ROM.…”
Section: Discussionsupporting
confidence: 90%
“…Yu et al [ 43 ] showed that activities directed toward the restoration of movement, such as the use of “over-ground” treadmill training (as shown in people to improve motor recovery and balance (e.g., using proprioceptive platforms) may actually be more rational early on in the recovery process for paraplegia induced by intervertebral disc extrusion (IVDE) and should be encouraged first, but an “under-water” treadmill is best suited to improve strength and muscle mass. In human beings, assisted walking movement in patients with genetic and acquired neuromuscular disorders with a motorized Innowalk device gave better results [ 44 ]. Using an intensive neurorehabilitation (INR) training protocol based on the evidence of signal transmission throughout the lesion caudally and rostrally, which can be detected by electromyography, and a multimodal approach, which included locomotor training, electrostimulation protocols, and, in circumstances of absent deep pain perception, pharmacological management, in dogs previously treated with hemilaminectomy for IVDE, Martins et al [ 45 ] obtained an ambulation rate of 58.5% within a maximum of 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standardized physiotherapy program followed across the board, making it difficult to compare results between studies. The type of physiotherapy shown to improve locomotor outcomes in experimental injury models, and employed in people with severe injuries, is a very intensive type of locomotor training [ 44 ]. The therapeutic activities implemented in veterinary medicine classically include treadmill walking, passive range of motion exercises, and assisted weight-supported walking.…”
Section: Discussionmentioning
confidence: 99%
“…The Innowalk device is a motorized, multi-functional assistive device offering the possibility of repetitive leg movements in an upright individually adjusted weight-bearing position (5). This movement induces flexion and extension of hip, knee and ankle joints.…”
Section: Innowalk Devicementioning
confidence: 99%